(untitled) (Medicine Today, 2019)
Introduction: To evaluate knowledge about anemia among pregnant women visiting in OPD for antenatal care. Materials and Methods: A cross sectional study was conducted in tertiary hospital Dhaka, from outdoor patient department of gynecology and obstetrics, to assess the knowledge about anemia among pregnant women and also to find out the percentage and type of anemia. A total 396 pregnant women were interviewed and information were collected by pre designed data collection sheet using various parameters. Interviews conducted by direct questionnaire, blood samples were collected at same setting. Results: The mean age was 25.92±5.05, highest number 39.65% were age group 21-25 years, 28.79% were age group -30 years, 15.91% were age group 31-35 years, 11.36% were found age group <20 years. Regarding antenatal visit during pregnancy, 25.8% pregnant women visited in 1st trimester, 46.7% pregnant women visited in second trimester, and 27.5% in 3rd trimester. Also 11.11% patients had anemia in first trimester, 39.39% anemic in 2nd trimester, 14.39% pregnant women anemic in third trimester and 35.10% had normal findings. And 67% pregnant woman’s had knowledge about ANC 32% had no knowledge. Conclusion: In this cross sectional study it was found that poor knowledge about anemia and less iron intake is the main cause for anemia during pregnancy. Medicine Today 2019 Vol.31(2): 105-110